RESULTS OF TREATMENT OF ACUTE LUMBAR DISC HERNIATION WITH TRANSFORAMINAL NERVE ROOT BLOCK - VIALLE,EMILIANO NEVES (2016)
ABSTRACT Objective: To determine the efficacy of anesthetic transforaminal nerve root block in patients with sciatica secondary to lumbar disc herniation through a prospective observational study. Methods: The study included 176 patients from a private clinic undergoing transforaminal injection performed by a single spinal surgeon. The patients were assessed after two weeks, three months and six months regarding to the improvement of the pain radiating to the lower limbs. In case of persistent symptoms, patients could choose to perform a new nerve root block and maintenance of physical therapy or be submitted to conventional microdiscectomy. Results: By the end of six-month follow-up of the 176 patients, 116 had a favorable outcome (95 after one block and 21 after two blocks), and only 43 required surgery. Conclusion: The results of our study suggest a positive effect of transforaminal block for the treatment of sciatica in patients with lumbar disc herniation.